PEMBUATAN ABON IKAN PATIN (Pangasius hypophthalmus) DI PRADIPTA JAYA FOOD PROBOLINGGO - Ismi Jasila; Fadilatuz Zahro (Samakia : Jurnal Ilmu Perikanan, 2015)
The purpose of this study was to determine the processing of shredded catfish (Pangasius hypophthalmus), knowing the nutrient content in the shredded catfish and shredded catfish production costs in Pradipta Jaya Food Bulk Grinting Probolinggo. The study was conducted over three (3) months, from February 2015 to April 2014. The method used in this study is a survey, primary data collected by field observation, participation, interviews, and documentation. Secondary data was collected through literature. Based on the results of the research can be informed that the processing of shredded catfish (Pangasius hypophthalmus) conducted in Pradipta Jaya Food Probolinggo include the following stages: receipt of raw materials, weighing first, washing, steaming, weeding, filtration (draining), the first milling, weighing both , mixing spices, oven, milling second, sieving, third weighing, packaging, storage, and marketing. Shredded catfish containing 43.30% protein content, fat content of 10.50%, 2.37% moisture content, carbohydrate content of 37.35%, gross profit earned on each product shredded catfish Rp. 1.1139 million.